Underlying Mechanism and Active Ingredients of Tianma Gouteng Acting on Cerebral Infarction as Determined via Network Pharmacology Analysis Combined With Experimental Validation - Tang, Xiaolei; Lu, Jing; Chen, Haoyuan; Zhai, Lu; Zhang, Yuxin; Lou, Huijuan; Wang, Yufeng; Sun, Liwei; Song, Bailin (Frontiers in Pharmacology, 2021)
Cerebral infarction (CI), a common cerebrovascular disease in the world, remains to be the happen factors of many diseases including hypokalemia, respiratory diseases, and lower extremity venous thrombosis. Tianma Gouteng (TMGT) is reported to be a Traditional Chinese Medicine (TCM) prescription in the clinical treatment of CI. In this study, high-performance liquid chromatography(HPLC) fingerprint analysis was used to detect the major chemical compositions of TMGT.TCMSP and BATMAN-TCM databases were used to screen the active compounds of TMGT, while GeneCards database was used to screen the protein targets with CI. GO and KEGG enrichment analysis of these core nodes are performed to determine the key biological processes and signal pathways. A total of 6 possible gene including NFKBIA, PPARA, IL6, IL1B, CXCL8, and HIF1A were selected. PC12 cells were treated under glucose and oxygen deprivation (OGD) condition to induce OGD cell model while BV2 cells were induced with lipopolysaccharide (LPS) to stimulate inflammation model of CI. TM-GT treatment increased the expression of PPARγ and downregulated the expression of p-P65, IκBα and HIF-1α in OGD and LPS-induced cell models. Molecular docking showed that quercetin in TMGT may be an active substance involved in the processes of CI. Data in this research revealed that TMGT could inhibit neuro-inflammatory and improve the nerve damage under OGD condition in brain cells through the HIF-1α/PPARγ/NF-κB pathway, implying the possible application of TMGT at the clinical application in treating CI.